Aedes Mosquito Dynamics: Unravelling Behavior, Genetics, and Arbovirus Risks in India - Preeti Acharya; Showkat Ahmad Mir; Binata Nayak (Gonabad University of Medical Sciences, 2024)
Background: Aedes aegypti and Aedes albopictus responsible for transmitting severe viruses, such as dengue, chikungunya, yellow fever, and Zika, pose a significant health threat in India. Challenges in vector control, including insecticide resistance and limited progress in vaccine development, coupled with factors like climate change and urbanization, contribute to an extensive expansion of mosquito habitats and disease transmission. However, the existing literature on how these factors influence mosquito behavior, genetic architecture, and virus transmission patterns in different regions of India is insufficient. Methods: This scoping review conducted a thorough search across online databases, such as Google Scholar, Web of Science, Scopus, and PubMed. The keywords that were used were as follows: "Ae. Aegypti," "Ae. albopictus," "breeding habitat," "feeding preference," "genetic diversity," "virus transmission," "dengue," "chikungunya," "Zika," and "India." The online search, conducted from October to November 2023, focused on English-language articles from 2013 to November 2023. The inclusion criteria encompassed articles addressing Aedes behavior, genetic diversity, and disease transmission, while the exclusion criteria removed non-Aedes mosquito studies and duplicates. Article quality was manually checked and assessed. Results: The literature survey spanning the past ten years categorized the data into the following four subgroups: "Arboviral disease," "arbovirus transmission," "Aedes mosquito behavior," and "genetic diversity." The data synthesis emphasized the need to focus on Aedes mosquito breeding habitats and virus transmission patterns in common dengue endemic regions, like Delhi, Tamil Nadu, Kerala, Rajasthan, and Uttar Pradesh in India. However, research on feeding behavior and genetic diversity is scarce. Hence, more research should be conducted in these areas.  Conclusion: This analysis highlights critical gaps in our understanding, emphasizing the necessity for detailed mapping, studying virus evolution, socio-epidemiological research, and using advanced technologies for real-time monitoring. Understanding the complex relationships between blood-feeding patterns, host preferences, and diverse breeding habitats is crucial for effective disease control.